LncRNA SOX2-OTinhibitionprotects against myocardialischemia/reperfusion-inducedinjury via themicroRNA-186-5p (miR-186-5p)/Yin Yang 1 (YY1)pathway. Issue 1 (1st January 2022) - Yang, Pengjie; Liang, Kun; Wang, Weisong; Zhou, Dehua; Chen, Yuan; Jiang, Xueyan; Fu, Rong; Zhu, Benben; Lin, Xuefeng
ABSTRACT: Long noncoding RNAs (lncRNAs) exert essential effects in regulating myocardial ischemia/reperfusion (MI/R)-induced injury. This work intended to explore the functions of lncRNA SOX2-OT and its regulatory mechanism within MI/R-induced injury. In this study, gene expression was determined by RT-qPCR. Western blotting was applied for the detection of protein levels. Pro-inflammatory cytokine concentrations, cardiomyocyte viability, and apoptosis were detected via ELISA, CCK-8 and flow cytometry. In the in vitro model, SOX2-OT and YY1 were both upregulated, while miR-186-5p was downregulated. SOX2-OT knockdown attenuated oxygen-glucose deprivation/reoxygenation (OGD/R)-induced cardiomyocyte dysregulation through relieving inflammation, promoting proliferation, and reducing apoptosis in OGD/R-treated H2C9 cells. SOX2-OT positively regulated YY1 expression via miR-186-5p. Moreover, miR-186-5p inhibition or YY1 upregulation abolished the effects of SOX2-OT blocking on the inflammatory responses, proliferation, and apoptosis of OGD/R-challenged H2C9 cells. In conclusion, our results, for the first time, demonstrated that SOX2-OT inhibition attenuated MI/R injury in vitro via regulating the miR-186-5p/YY1 axis, offering potential therapeutic targets for MI/R injury treatment.